The Use of Lamtoro Plants as Organic Fertilizers for Cayenne Pepper Plants of Local Varieties (Capsicum frutescens L.) - Nur Aini Bunyani; Robert A. Sole; Joritha Naisanu (Jurnal Biologi Tropis, 2021)
Lamtoro is a dry land plant that is widely found in East Nusa Tenggara. The abundant availability of this plant causes this plant to be of no economic value. On the other hand, this plant contains a lot of nitrogen which can be used to supply nutrients for plants, by utilizing the leaf extract.Lamtoro leaf extract can be used as organic fertilizer for chili plants, where this plant has economic value and is in great demand by the public. This study aimed to determine the effect of various concentrations of lamtoro leaf extract which showed the best results on cayenne pepper. This research has been carried out on farmers' land located in the Liliba Family, Oebobo District, Kupang City which took place from April 2020 to July 2020. The design used in this study was a randomized block design (RAK) with 5 treatments and 4 replications, with treatment P0 (control), P1 (administration of 200 ccliter of lamtoro extract concentration of water-1), P2 (administration of 250 ccliter of water-1 extract of Lamtoro concentration). ), P3 (Giving Concentration of Lamtoro Extract 300 ccliter water-1), P4 (Giving Concentration of Lamtoro Extract 350 ccliter water-1). The results of this study indicate that the treatment of lamtoro leaf extract has a very significant effect on plant height(111cm), number of leaves (221.25 pieces), number of fruit (175.25 pieces), and fruit weight (128,875 kg).